ANALISIS KARAKTER MANDIRI SISWA DENGAN PENDEKATAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Maya Sari; Mohammad Fauziddin; Masrul; Lusi Marleni; Mufarizuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze students' independent character through the implementation of differentiated instruction in the Science and Social Studies (IPAS) subject in Grade V at SDN 009 Bangkinang Kota. The background of the study is rooted in the importance of fostering independence in students from an early age and the need for instructional strategies that accommodate student diversity. This research employed a qualitative approach with a case study method. The research subjects were 18 fifth-grade students. Data were collected through observation, interviews, and documentation. The findings reveal that differentiated instruction supports the development of students' independent character, particularly in four key aspects: time management, resource management, problem-solving, and self-development. However, variations in the level of independence among students were observed, especially in problem-solving and self-development aspects. These results indicate that differentiated instruction provides a positive learning environment for nurturing student independence, although continuous guidance and support are still necessary. This study recommends that teachers continue to develop student-centered instructional strategies to foster more independent and responsible learners.